The Influence of Accountability and Transparency on PBB P2 Taxpayer Compliance in BAPENDA Bekasi City - Azimah Hanifah (Greenation Research & Yayasan Global Resarch National, 2023)
The aim of this research is to determine and analyze: (1) Accountability (2) Transparency; (3) Taxpayer Compliance; and (4) The influence of accountability and transparency on PBB P2 taxpayer compliance in BAPENDA Bekasi City, both simultaneously and partially. The research method used in this research is causality study, the unit of analysis in this research is PBB P2 taxpayer respondents in the Purwakarta Regency area. The type of investigation is causality, and the time horizon in this research is cross-sectional. Based on the research results, it was found that PBB P2 Tax Accountability in the Bekasi City Area is good, PBB P2 Tax Transparency in the Bekasi City Area can generally be said to be good, PBB P2 Taxpayer Compliance in the Bekasi City Area is currently considered good. Accountability and Transparency influence PBB P2 Taxpayer Compliance in BAPENDA Bekasi City simultaneously and partially. However, partially Accountability is dominant in influencing Taxpayer Compliance rather than Transparency Because Accountability is more dominant in influencing PBBP2 Taxpayer Compliance, it is the first priority in increasing PBBP2 Taxpayer Compliance. Therefore, BAPENDA Bekasi City is advised to consistently maintain existing accountability, so that the company's performance continues to improve.